ANALISIS KESALAHAN BERBAHASA PADA MEDIA LUAR RUANG DI KOTA PEKANBARU - Besus Heru Widodo; Elmustian Elmustian; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This article aims to analyze language errors in outdoor media in Pekanbaru City. There are still many errors in the writing of outdoor media so that it is a special concern for researchers to conduct this research. This research was conducted in a qualitative descriptive manner with the collection of observational data and documentation. Open data sources in the form of outdoor media in Pekanbaru City. The results showed that there were errors in writing punctuation marks, writing capital letters, writing level numbers, writing prepositions or prepositions, writing abbreviations, and titles.Keywords: language errors, outdoor media, pekanbaru city